Dual-doping to suppress cracking in spinel LiMn2O4: a joint theoretical and experimental study. Issue 9 (16th February 2016) - Zhang, Zhifeng; Chen, Zhenlian; Wang, Guangjin; Ren, Heng; Pan, Mu; Xiao, Lingli; Wu, Kuicheng; Zhao, Liutao; Yang, Jianqing; Wu, Qingguo; Shu, Jie; Wang, Dongjie; et al.
Abstract : Bonding Layout (purple line) of Mn 3+ (green balls) results in different unit cells (blue box), correlating to distinct cracking tendency in long-term charging-discharging cycling. Abstract : Electrochemical cycling stabilities were compared for undoped and Al/Co dual-doped spinel LiMn2 O4 synthesized by solid state reactions. We observed the suppression of particle fracture in Al/Co dual-doped LiMn2 O4 during charge/discharge cycling and its distinguishable particle morphology with respect to the undoped material. Systematic first-principles calculations were performed on undoped, Al or Co single-doped, and Al/Co dual-doped LiMn2 O4 to investigate their structural differences at the atomistic level. We reveal that while Jahn–Teller distortion associated with the Mn 3+ O6 octahedron is the origin of the lattice strain, the networking — i.e. the distribution of mixed valence Mn ions — is much more important to release the lattice strain, and thus to alleviating particle cracking. The calculations showed that the lattice mismatching between Li + intercalation and deintercalation of LiMn2 O4 can be significantly reduced by dual-doping, and therefore also the volumetric shrinkage during delithiation. This may account for the near disappearance of cracks on the surface of Al/Co–LiMn2 O4 after 350 cycles, while some obvious cracks have developed in undoped LiMn2 O4 at similar particle size even after 50 cycles. Correspondingly, Al/Co dual-doped LiMn2 O4 showed a good cycling stability with a capacity retention of 84.1% after 350 cycles at a rate of 1C, 8% higher than the undoped phase.